2012
DOI: 10.1007/s00228-012-1448-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage

Abstract: We identified ORM1 as another polymorphic gene affecting warfarin dose requirements. ORM1 S carriers require lower maintenance doses to achieve and maintain an optimal level of anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Therefore, combined contribution of VKORC1 rs9923231, CYP2C9 rs1057910, and ORM1 rs17650 polymorphisms to dosage variation in this study with a narrow participant population of specific genotypes was lower than those in our early study (14.8% vs 25.3%). 9 According to the INR records for our data (Figure 2), current warfarin treatment practices provided effective and safe anticoagulant therapy for the patients with wildtype genotypes in the first month. The INR of these patients rose quickly and remained steady within the target range.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Therefore, combined contribution of VKORC1 rs9923231, CYP2C9 rs1057910, and ORM1 rs17650 polymorphisms to dosage variation in this study with a narrow participant population of specific genotypes was lower than those in our early study (14.8% vs 25.3%). 9 According to the INR records for our data (Figure 2), current warfarin treatment practices provided effective and safe anticoagulant therapy for the patients with wildtype genotypes in the first month. The INR of these patients rose quickly and remained steady within the target range.…”
Section: Discussionmentioning
confidence: 92%
“…Genotypes for VKORC1 rs9923231 and CYP2C9 rs1057910 were determined by using a pyrosequencing method as described previously, 9 and genotypes for CYP4F2 rs2108622 and ORM1 rs17650 were determined through a Polymerase Chain Reaction (PCR)-restriction fragment length polymorphism method as described previously. 9 The CYP4F2 rs2108622 genotypes were differentiated using PvuII enzyme restriction digestion. The ORM1 rs17650 genotypes were differentiated using EcoNI enzyme restriction digestion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have reported substantial prevalence and significant effect on warfarin dose by these gene products. 24,[34][35][36]44,46,62,66,69,72 These polymorphisms may be considered to be prevalent and substantial contributors to warfarin dose variability in Pakistani population. Further studies on such polymorphisms are recommended to identify the major genetic factors in Pakistani population.…”
Section: Discussionmentioning
confidence: 99%
“…We used next-generation sequencing method to resequence the exons, exon-intron boundaries and gene regulatory regions of 43 target genes or regions that were potentially associated with warfarin dosage. These warfarin dose-associated genes or areas were selected on the basis of the PharmaGKB website, the results of genome-wide association studies, or the results of other published studies [17][18][19][20][21][22]. The details of these genes are shown in Fig linkage disequilibrium (LD) (r 2 > 0.9).…”
Section: Methodsmentioning
confidence: 99%